Do callers of young children with fever follow the self-care recommendations given by a nursing triage line? - Manji, Sofiya; Garner, Charlene; Steinlicht, Delores; Edwards, Sarah; McDonald, Sheila (International Journal of Population Data Science, 2018)
Introduction The management of fever can be a stressful situation for caregivers of young children. Accessing emergency departments and urgent care centres (ED/UCCs) due to concerns about fever and the potential consequences of child fever is common, despite fever rarely being considered a medical emergency. Objectives and Approach Determine the non-compliance rate with public health advice for self-care at home for young children (3-35 months) with a fever. Non-compliance was defined based on the presence of a record of healthcare use within 72 hours following a call to a nurse telephone triage line, Health Link (HL), and receiving a self-care recommendation. Callers between October 2015-March 2016 were identified and linked with four databases: registry files, National Ambulatory Care Reporting System; Inpatient-Discharge Abstract Database and Physician Claims (N = 879). Overall non-compliance rate and descriptive analysis by child age, caregiver age, geography, and call time were completed. Results The overall non-compliance rate with HL advice was 35.6%. Among callers, 17.5% visited an ED/UCC, 1.1% had an inpatient hospital admission, and 21.3% visited a physician’s office. Among the patients that utilized health care services after the HL call, 13.6% only visited ED/UCC, 18% only visited a physician’s office, and 4% utilized more than one type of health care service. Callers in rural and rural remote areas had lower odds of visiting a physician’s office compared to the urban areas (p-value <0.01). No significant differences were found by child age, caregiver age or time of call. Conclusion/Implications Findings of this study suggest that approximately one-third of callers are not following the telephone triage advice, potentially leading to unnecessary increased burden on the healthcare system. Further study is warranted to examine reasons for non-compliance. Strategies to increase compliance in caregivers should be explored.